Super-oleophylic and super-hydrophobic surface modified non-woven fabric as well as preparation method and application thereof
By modifying the three-dimensional hierarchical structure and light-responsive properties of the modified non-woven fabric, the high energy consumption, high cost and secondary pollution problems of the existing oil-water separation technology are solved, and efficient and stable oil-water separation and organic pollutant degradation are achieved, which is suitable for the oil-water separation needs of industrial and marine environments.
Patent Information
- Application Number
- CN202510725113.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-09-16
AI Technical Summary
Existing oil-water separation technologies have problems such as high energy consumption, high cost, easy secondary pollution and low separation efficiency. In particular, traditional membrane separation technology is not effective in treating emulsified oil, and existing superhydrophobic and superoleophilic materials are mostly difficult-to-degrade polymers, which cause serious pollution.
It is made of a non-woven fabric base through a needle-punching/hydroentanglement process, combined with a MOFs nanoparticle layer, a polyelectrolyte middle layer and a light-responsive outer layer. Through in-situ growth, layer-by-layer self-assembly and photocatalytic treatment, a super-oleophilic and super-hydrophobic surface is formed. Combined with a micro-groove array and an alumina protective layer, efficient oil-water separation and organic pollutant degradation are achieved.
It achieves efficient and stable oil-water separation and organic pollutant degradation, has excellent acid and alkali resistance, is applicable to a wide temperature range, is suitable for oily wastewater treatment and marine oil spill emergency recovery, has light control properties and high oil absorption rate, and meets the needs of industrial and marine environments.
Smart Images

Figure BDA0005430328710000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material modification, in particular to a super-oleophilic and super-hydrophobic surface-modified non-woven fabric and a preparation method and application thereof. Background Art
[0002] The generation of oil-water mixtures is extremely common in numerous fields, including industrial production, daily life, and marine activities. Whether it is oily wastewater discharged from industries such as chemical and food processing, or oil spills that may occur during marine transportation, oil-water mixtures not only pose a serious threat to the ecological environment, such as polluting water resources and damaging marine ecosystems, but also affect the normal operation of production processes, reducing production efficiency and increasing production costs.
[0003] Traditional oil-water separation technologies, such as flotation, flocculation, adsorption, electro-dehydration, and chemical demulsification, have numerous drawbacks. Flotation requires significant energy to generate bubbles for oil-water separation; flocculation relies on the addition of chemicals, which not only increases treatment costs but also produces large quantities of difficult-to-treat sludge. Adsorption is limited by the adsorption capacity of the adsorbent material and is difficult to regenerate. Electro-dehydration requires specialized equipment and consumes significant energy. Chemical demulsification introduces new chemicals, potentially causing secondary environmental pollution.
[0004] Ultrafiltration membrane separation technology, as a physical method, requires no external chemicals and has a relatively simple process. It can remove difficult-to-treat emulsified and dissolved oils. However, traditional membrane separation technology is mainly based on the principle of pore size screening. To separate dissolved and emulsified oils, the separation membrane pore size must be extremely small (less than 0.1μm or even less than 10nm). This results in low porosity and high filtration resistance, forcing higher operating pressures. However, increased operating pressures can easily cause oil droplets to deform and pass through the separation membrane, resulting in reduced separation efficiency.
[0005] In recent years, with the development of biomimetic technology, research on the super-hydrophobic and super-hydrophilic phenomena of natural plants and animals has continued to deepen. Using special wettability surfaces for oil-water separation has become a hot topic in functional materials research. For example, patent application number CN106178599A discloses a self-cleaning polybenzoxazine super-hydrophobic and super-oleophilic mesh material, its preparation, and its application in oil-water separation. The super-hydrophobic and super-oleophilic mesh material comprises: 1 part by weight of benzoxazine, 0.001 to 60 parts by weight of nanoparticles, and 1 to 100 parts by weight of a solvent. The preparation process involves adding the nanoparticles to a benzoxazine solution and mixing and dispersing them uniformly; placing a polymer fiber filter cloth or metal filter screen in the mixture, and preparing the self-cleaning polybenzoxazine super-hydrophobic and super-oleophilic mesh material by a pull-coating method and further thermal curing. The invention provides a super-hydrophobic and super-oleophilic mesh material and its preparation method with excellent oil-water separation properties, which is cheap in raw materials, free of fluorine-containing additives, simple in process, and suitable for continuous industrial production. The oil-water separation material is resistant to acid and alkali, UV radiation, and high temperature, can be recycled multiple times, and has good self-cleaning properties under the combined action of light and heat treatment. However, existing special wettability materials with oil-water separation functions, including the self-cleaning polybenzoxazine super-hydrophobic and super-oleophilic mesh material prepared in the above scheme, are mostly composed of non-degradable or difficult-to-degrade polymer materials. When treating oily wastewater, the oleophilic oil-water separation material is easily contaminated due to its oleophilic nature. After use, a large amount of difficult-to-treat contaminated garbage and waste will be generated, which not only easily causes secondary pollution to the environment, but also has a high overall cost for post-processing, which seriously restricts the practical application of oil-water separation materials. Summary of the Invention
[0006] The purpose of the present invention is to provide a super-oleophilic and super-hydrophobic surface modified non-woven fabric and its preparation method and application, so as to solve the problems raised in the above background technology.
[0007] To achieve the above object, the present invention provides a super-oleophilic and super-hydrophobic surface-modified non-woven fabric, comprising:
[0008] Non-woven fabric substrate: Made of PP polypropylene or PET polyester fibers with a diameter of 5-20 μm through needle punching / spunlace process, with a unit area mass of 80-200 g / m 2 ;
[0009] Three-dimensional graded modified layer, comprising:
[0010] MOFs nanoparticle layer: in situ grown ZIF-8 or MOF-5 nanoparticles (particle size 30-80 nm), covalently bonded to the amino groups on the substrate surface through coordination bonds, with a thickness of 2-5 μm;
[0011] Polyelectrolyte interlayer: 5-10 layers of PSS polystyrene sulfonate and PDDA polydiallyldimethylammonium chloride are alternately deposited, with a total thickness of 50-200 nm;
[0012] Photoresponsive outer layer: azobenzene-modified perfluoropolyether (PFPE-AZO) coating (grafting density ≥ 1.2 mmol / m 2 ), the surface energy under ultraviolet light is reduced from 12mN / m to 8mN / m;
[0013] The water contact angle of the modified non-woven fabric is ≥160°, the oil contact angle is ≤5°, the oil absorption rate is ≥25g / g, and the separation flux is ≥12000L / (m 2 h), acid and alkali resistance (pH 2-12) performance retention rate ≥ 90% after 500 cycles.
[0014] Preferably, the MOFs nanoparticles are in-situ grown by a solvent thermal method, with a loading of 30-50 wt%, and are chemically bonded to the non-woven fabric substrate via a titanium metal transition layer with a thickness of 5-20 nm, with a bonding strength of ≥5 N / cm.
[0015] Preferably, the photoresponsive outer layer is grafted by ultraviolet light-induced polymerization to form a cross-linked network with a thickness of 10-30 nm, and the wettability switching is completed within 30 seconds under 365 nm light.
[0016] Preferably, the surface of the modified nonwoven fabric is etched by pulsed laser to form a micro-groove array with a depth of 5-15 μm, and the spacing between adjacent micro-grooves is 20-50 μm, which cooperates with the nanostructure to construct a directional oil guide channel.
[0017] On the other hand, the present invention also provides a method for preparing a super oleophilic and super hydrophobic surface modified non-woven fabric, which is used to prepare the above-mentioned super oleophilic and super hydrophobic surface modified non-woven fabric, comprising:
[0018] S10, substrate pretreatment:
[0019] S11: immersing the non-woven fabric in an ethanol solution containing 0.1-2 wt% polyethyleneimine (PEI) and ultrasonically treating the solution at 50-80° C. for 10-30 min to form a cationic adsorption layer;
[0020] S12: depositing a 5-20 nm thick titanium metal transition layer on the substrate surface by radio frequency magnetron sputtering;
[0021] S20, MOFs in situ growth:
[0022] The pretreated non-woven fabric was immersed in a methanol solution containing 0.2-0.5M zinc nitrate and 0.5-1.0M 2-methylimidazole, and the reaction was hydrothermally reacted at 80-120°C for 6-18 hours. The pH was adjusted to 4.5-5.5 to form a ZIF-8 nanoparticle layer. The unreacted substances were removed by centrifugation and ethanol washing, and the MOFs-modified non-woven fabric was obtained after vacuum drying.
[0023] S30, surface functionalization:
[0024] S31: First, the MOFs-modified non-woven fabric is immersed in a toluene solution of 3-aminopropyltrimethoxysilane at a concentration of 1-5 wt % and reacted at 60-90° C. for 2-4 h to introduce amino active sites;
[0025] S32: alternately depositing sodium polystyrene sulfonate and polydiallyldimethylammonium chloride using a layer-by-layer self-assembly technique to form a polyelectrolyte composite membrane with a thickness of 50-200 nm;
[0026] S33: Finally, ultraviolet light-induced polymerization is performed to graft the perfluoropolyether containing azobenzene groups, with the grafting rate being controlled at 8-15 wt %;
[0027] S40, interface strengthening treatment:
[0028] The modified nonwoven fabric prepared in step S30 is placed in a carbon dioxide supercritical fluid at 10-20 MPa and 40-60° C. for 30-60 minutes to promote interface fusion of the materials;
[0029] Pulsed laser deposition technology is used to etch micro-grooves on the surface with a depth of 5-15μm and a spacing of 20-50μm to form directional oil-conducting channels;
[0030] S50, functional synergistic modification:
[0031] Nano-titanium dioxide sol is introduced for post-treatment to generate hydroxyl radicals in situ on the surface of the non-woven fabric through photocatalytic reaction, achieving synergistic function of oil degradation;
[0032] ALD atomic layer deposition technology is used to deposit a 5-10 nm thick aluminum oxide protective layer on the surface to enhance acid and alkali resistance, thereby obtaining the final super-oleophilic and super-hydrophobic surface modified non-woven fabric.
[0033] Preferably, in step S20 , a surfactant of 0.01-0.05 M is added to the MOFs growth solution, wherein the surfactant is CTAB hexadecyltrimethylammonium bromide, to adjust the uniformity of particle size, and the CV value is less than 15%.
[0034] Preferably, in step S30, the polyelectrolyte membrane is formed by electrostatic adsorption, the deposition time of each layer is 10-30 minutes, and the solution concentration is 0.5-2 wt%.
[0035] Preferably, the post-treatment of the nano-titanium dioxide sol in step S50 is achieved by an immersion-coating method, with a loading amount of 1-3 wt % and a degradation rate of benzene series substances under visible light of ≥90%.
[0036] In addition, the present invention also provides an application of a super oleophilic and super hydrophobic surface modified non-woven fabric. The super oleophilic and super hydrophobic surface modified non-woven fabric can be used for:
[0037] Light-controlled oil-water separation system, which achieves selective adsorption through ultraviolet / visible light switching;
[0038] Oily wastewater treatment, simultaneous completion of oil-water separation and organic pollutant degradation;
[0039] Marine oil spill emergency recovery, the removal rate of emulsified oil with oil droplet size of 5-50μm is ≥98%.
[0040] Preferably, the modified non-woven fabric can be recycled, and the separation efficiency is still ≥95% after 500 light response switchings, and is suitable for a wide temperature range environment of -40°C to 120°C.
[0041] Compared with the prior art, the present invention has the following beneficial effects:
[0042] 1. Product performance
[0043] The super-oleophilic and super-hydrophobic properties are outstanding: the water contact angle is ≥160°, and the oil contact angle is ≤5°. It can clearly distinguish between water and oil in the oil-water mixed system and efficiently separate oil and water, greatly improving the practicality of non-woven fabrics in scenarios such as oily wastewater treatment and marine oil spill emergency recovery.
[0044] High oil absorption rate: The oil absorption rate reaches 24-30g / g. Thanks to the increased specific surface area of the MOFs nanoparticle layer and the optimization of the surface chemical properties by the polyelectrolyte middle layer and the light-responsive outer layer, it can absorb a large amount of oil substances, improve the ability to treat oil pollution in a single time, and reduce the number of treatment processes.
[0045] High separation flux: separation flux is 12200-13500L / (m 2 h), the directional oil-conducting channels constructed in collaboration with the reasonable micro-groove array and nanostructure, combined with good surface properties, enable oil substances to quickly pass through the non-woven fabric, greatly improving the oil-water separation efficiency and meeting the needs of large-scale industrial applications.
[0046] Excellent acid and alkali resistance: After 500 cycles of acid and alkali resistance (pH 2-12), the performance retention rate is ≥90%. The aluminum oxide protective layer deposited by ALD atomic layer deposition technology effectively enhances the acid and alkali resistance of the non-woven fabric, broadening its application range in different acid and alkali environments, for example, it has more advantages in chemical wastewater treatment.
[0047] Good light-control performance: In the light-controlled oil-water separation system, the separation efficiency is ≥95% after 500 light-response switching. The rational design and preparation of the light-responsive outer layer enables the non-woven fabric to stably achieve selective adsorption under ultraviolet / visible light switching, realizing precise and controllable oil-water separation operations, and can be applied to intelligent oil-water separation equipment.
[0048] Wide Temperature Range Applicability and High Emulsified Oil Removal Rate: The product operates across a wide temperature range of -40°C to 120°C, achieving a removal rate of ≥98% for emulsified oil droplets ranging from 5-50μm. The stable overall material structure ensures wide temperature range applicability. Its super-oleophilic and super-hydrophobic properties, combined with its microstructure, effectively treat emulsified oil, making it highly effective even in complex temperature environments, such as polar regions or high-temperature industrial environments.
[0049] 2. Preparation Method
[0050] Strong process synergy: Through a series of steps, including substrate pretreatment, in-situ MOF growth, surface functionalization, interface enhancement, and functional synergistic modification, each process works in synergy. For example, substrate pretreatment provides a good foundation for the subsequent growth of MOF nanoparticles, while in-situ MOF growth determines key properties such as specific surface area. Subsequent surface functionalization further optimizes performance, resulting in a significant synergistic effect that significantly enhances product performance.
[0051] High parameter controllability: During the growth of MOFs, the addition of surfactants can adjust the uniformity of particle size (CV value <15%); the polyelectrolyte membrane is precisely controlled by controlling the deposition time of each layer (10-30min) and the solution concentration (0.5-2wt%); parameters such as the nano-titanium dioxide sol loading (1-3wt%) can be flexibly adjusted, making it easy to customize product performance according to different application requirements.
[0052] Innovative technological applications: A series of advanced technologies such as radio frequency magnetron sputtering to deposit titanium metal transition layer, layer-by-layer self-assembly technology to alternately deposit polyelectrolytes, ultraviolet light-induced polymerization to graft photoresponsive outer layer, carbon dioxide supercritical fluid treatment to promote interface fusion, pulsed laser deposition technology to etch micro-groove arrays, and ALD atomic layer deposition technology to deposit aluminum oxide protective layer are used to ensure the realization and improvement of product performance.
[0053] 3. In terms of application
[0054] Application advantages of the light-controlled oil-water separation system: Selective adsorption can be achieved through ultraviolet / visible light switching, and it can provide efficient and precise separation operations in scenarios where precise control of oil-water separation is required, such as laboratory trace oil-water separation experiments and oil-water separation links on specific industrial production lines.
[0055] Advantages of oily wastewater treatment: Synchronous completion of oil-water separation and organic pollutant degradation. When treating oily wastewater, it can not only separate oil and water, but also use nano-titanium dioxide sol post-treatment to achieve a degradation rate of organic pollutants such as benzene series ≥ 90%, reduce secondary pollution, reduce subsequent treatment costs, and meet environmental protection requirements.
[0056] Marine Oil Spill Emergency Recovery Advantages: The removal rate for emulsified oil with a droplet size of 5-50μm is ≥98%. During marine oil spill emergency response, this device can quickly and efficiently recover emulsified oil, reducing marine environmental pollution and protecting marine ecosystems. Furthermore, it is recyclable, with a separation efficiency of ≥95% after 500 light response cycles. It is suitable for use in a wide temperature range of -40°C to 120°C, ensuring its effectiveness in diverse marine environments. DETAILED DESCRIPTION
[0057] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0058] Example 1
[0059] A super-oleophilic and super-hydrophobic surface-modified non-woven fabric and a preparation method thereof, comprising:
[0060] Non-woven fabric base: PP polypropylene fiber with a diameter of 10μm is selected and made by needle punching process, with a unit area mass of 120g / m2.
[0061] Three-dimensional graded modified layer, comprising:
[0062] MOFs Nanoparticle Layer: ZIF-8 nanoparticles are grown in situ using a solvothermal method, with a particle size of approximately 50 nm. The nanoparticle loading is 40 wt%, chemically bonded to the nonwoven fabric substrate via a 10 nm thick titanium transition layer, achieving a bond strength of 6 N / cm.
[0063] Polyelectrolyte intermediate layer: 8 layers of PSS polystyrene sulfonate sodium and PDDA polydiallyldimethylammonium chloride were alternately deposited, with each layer deposition time of 20 min and a solution concentration of 1 wt %. The final total thickness reached 120 nm.
[0064] Photoresponsive outer layer: a perfluoropolyether coating modified with azobenzene grafted via UV-induced polymerization, with a grafting density of 1.5 mmol / m 2 Under 365nm light irradiation, the wettability switching was completed within 30s, forming a cross-linked network with a thickness of 20nm.
[0065] Other treatments:
[0066] The surface of the modified nonwoven fabric is etched by pulsed laser to form a microgroove array with a depth of 8 μm and a spacing of 30 μm between adjacent microgrooves.
[0067] The preparation process follows steps S10-S50. In S20, 0.03M CTAB (cetyltrimethylammonium bromide) is added to the MOF growth solution as a surfactant to control particle size uniformity, achieving a CV value of 12%. In S30, the polyelectrolyte film is formed by electrostatic adsorption. In S50, the nano-titanium dioxide sol is post-treated using an immersion-coating method, achieving a 2wt% loading and a 92% degradation rate for benzene derivatives under visible light.
[0068] Performance test: water contact angle is 165°, oil contact angle is 3°, oil absorption rate is 28g / g, separation flux is 13000L / (m 2 h), acid and alkali resistance (pH 2-12) with a performance retention rate of 92% after 500 cycles. In a light-controlled oil-water separation system, the separation efficiency reached 96% after 500 light response switching cycles. Performance was stable over a wide temperature range of -40°C to 120°C. The removal rate for emulsified oil with a droplet size of 5-50μm was 98.5%.
[0069] Example 2
[0070] A super-oleophilic and super-hydrophobic surface-modified non-woven fabric and a preparation method thereof, comprising:
[0071] Non-woven fabric base: Made of PET polyester fiber with a diameter of 15μm, made by hydroentanglement process, with a unit area mass of 150g / m2.
[0072] Three-dimensional graded modified layer, comprising:
[0073] MOFs nanoparticle layer: In situ grown MOF-5 nanoparticles with a particle size of approximately 60nm and a loading of 35wt%. Chemically bonded to the non-woven fabric substrate via a 15nm thick titanium metal transition layer with a bonding strength of 5.5N / cm.
[0074] Polyelectrolyte intermediate layer: 6 layers of PSS and PDDA were deposited alternately, with each layer deposition time of 15 min, solution concentration of 1.5 wt%, and total thickness of 100 nm.
[0075] Photoresponsive outer layer: grafted azobenzene-modified perfluoropolyether coating with a grafting density of 1.3 mmol / m 2 , the wettability switching was completed within 30s under 365nm light, forming a cross-linked network with a thickness of 15nm.
[0076] Other treatments:
[0077] Pulse laser etching formed a micro-groove array with a depth of 10 μm and a spacing of 40 μm between adjacent micro-grooves.
[0078] In step S20, 0.02M CTAB was added to the MOF growth solution, resulting in a particle size uniformity CV value of 13%. S30 The polyelectrolyte film was formed by electrostatic adsorption. S50 The nano-titanium dioxide sol had a loading of 1.5wt% and a degradation rate of 91% for benzene series under visible light.
[0079] Performance test: water contact angle 163°, oil contact angle 4°, oil absorption rate 26g / g, separation flux 12500L / (m 2 h), acid and alkali resistance (pH 2-12) with a performance retention rate of 91% after 500 cycles. The light-controlled oil-water separation system achieved a separation efficiency of 95.5% after 500 light-response switching cycles and is suitable for environments ranging from -40°C to 120°C. The removal rate for emulsified oil with a droplet size of 5-50μm was 98.2%.
[0080] Example 3
[0081] A super-oleophilic and super-hydrophobic surface-modified non-woven fabric and a preparation method thereof, comprising:
[0082] Non-woven fabric base: PP polypropylene fiber with a diameter of 8μm, needle punching process, unit area mass 100g / m 2 .
[0083] Three-dimensional graded modified layer, comprising:
[0084] MOFs nanoparticle layer: grow ZIF-8 nanoparticles with a particle size of 40 nm and a loading of 45 wt%, a titanium metal transition layer with a thickness of 8 nm and a bonding strength of 6.5 N / cm.
[0085] Polyelectrolyte intermediate layer: 10 layers of PSS and PDDA were deposited, with each layer deposition time of 30 min, solution concentration of 0.5 wt %, and a total thickness of 180 nm.
[0086] Photoresponsive outer layer: grafting density 1.4mmol / m 2 The wettability switching was completed within 30s under 365nm light, and the cross-linked network thickness was 25nm.
[0087] Other treatments:
[0088] The microgroove array has a depth of 6 μm and a pitch of 25 μm.
[0089] The addition of 0.04M CTAB to the MOF growth solution in S20 resulted in a particle size uniformity CV value of 14%. The S30 polyelectrolyte membrane was formed by electrostatic adsorption. The S50 nano-titanium dioxide sol had a loading of 2.5wt% and a degradation rate of 93% for benzene derivatives under visible light.
[0090] Performance test: water contact angle 168°, oil contact angle 2°, oil absorption rate 30g / g, separation flux 13500L / (m 2 -h), and 93% performance retention after 500 cycles of acid and alkali resistance (pH 2-12). The optically controlled oil-water separation system achieved a separation efficiency of 97% after 500 light-responsive switching cycles, with excellent performance over a wide temperature range of -40°C to 120°C. The removal rate for emulsified oil with a droplet size of 5-50μm was 99%.
[0091] Example 4
[0092] A super-oleophilic and super-hydrophobic surface-modified non-woven fabric and a preparation method thereof, comprising:
[0093] Non-woven fabric base: PET polyester fiber with a diameter of 20μm, spunlace process, unit area weight 200g / m 2 .
[0094] Three-dimensional graded modified layer, comprising:
[0095] MOFs nanoparticle layer: MOF-5 nanoparticles, particle size 80 nm, loading amount 32 wt%, titanium metal transition layer thickness 20 nm, bonding strength 5 N / cm.
[0096] Polyelectrolyte intermediate layer: 5 layers of PSS and PDDA were deposited, with each layer deposition time of 10 min, solution concentration of 2 wt%, and a total thickness of 80 nm.
[0097] Photoresponsive outer layer: grafting density 1.2mmol / m 2 The wettability switching was completed within 30s under 365nm light, and the cross-linked network thickness was 10nm.
[0098] Other treatments:
[0099] The microgroove array has a depth of 12 μm and a pitch of 50 μm.
[0100] S20: Adding 0.01M CTAB to the MOF growth solution resulted in a particle size uniformity CV value of 10%. S30: Polyelectrolyte membrane formed by electrostatic adsorption. S50: Nano-titanium dioxide sol loading of 1wt%, with a 90% degradation rate for benzene derivatives under visible light.
[0101] Performance test: water contact angle 162°, oil contact angle 5°, oil absorption rate 24g / g, separation flux 12200L / (m 2 h), acid and alkali resistance (pH 2-12) with a performance retention rate of 90% after 500 cycles. The optically controlled oil-water separation system achieved a separation efficiency of 95% after 500 light-responsive switching cycles and operated normally over a wide temperature range of -40°C to 120°C. The removal rate for emulsified oil with a droplet size of 5-50μm was 98%.
[0102] Comparative Example 1
[0103] A super-oleophilic and super-hydrophobic surface-modified non-woven fabric and a preparation method thereof, comprising:
[0104] Non-woven fabric substrate: PP polypropylene fiber with a diameter of 12μm, needle punching process, unit area mass 130g / m2.
[0105] Three-dimensional graded modified layer, comprising:
[0106] MOFs nanoparticle layer: No titanium metal transition layer was used, and ZIF-8 nanoparticles were directly loaded on the substrate with a loading of 30wt% and a bonding strength of only 3N / cm.
[0107] Polyelectrolyte intermediate layer: 4 layers of PSS and PDDA were deposited alternately, with each layer deposition time of 5 min, solution concentration of 0.3 wt%, and total thickness of 40 nm.
[0108] Photoresponsive outer layer: grafted azobenzene-modified perfluoropolyether coating, grafting density 1.0 mmol / m 2 , the wettability switching time under light is 60s, and the thickness of the cross-linked network is thin and uneven.
[0109] Other treatments: No pulsed laser etching of the microgroove array was performed. No surfactant was added to the MOF growth solution in S20, resulting in non-uniform particle size and a CV value of 25%. Insufficient polyelectrolyte film deposition was performed in S30. No post-treatment of the nano-titania sol and deposition of an alumina protective layer were performed in S50.
[0110] Performance test: water contact angle 150°, oil contact angle 10°, oil absorption rate 18g / g, separation flux 8000L / (m 2 h), acid and alkali resistance (pH 2-12) performance decreased significantly after 100 cycles, with a retention rate of only 70%. The light-controlled oil-water separation system exhibited unstable light response switching and low separation efficiency, and barely functioned after 500 cycles. The removal rate for emulsified oil with droplet sizes of 5-50 μm was only 70%.
[0111] Comparative Example 2
[0112] A super-oleophilic and super-hydrophobic surface-modified non-woven fabric and a preparation method thereof, comprising:
[0113] Non-woven fabric base: PET polyester fiber with a diameter of 18μm, spunlace process, unit area weight 180g / m 2 .
[0114] Three-dimensional graded modified layer, comprising:
[0115] MOFs nanoparticle layer: MOF-5 nanoparticles were loaded by ordinary physical adsorption, with a loading amount of 25 wt%, and the binding was not strong.
[0116] Polyelectrolyte intermediate layer: In an attempt to simplify the process, only one layer of PSS and PDDA mixed solution was deposited with a total thickness of 30 nm, which failed to form an effective composite membrane.
[0117] Photoresponsive outer layer: The grafted perfluoropolyether is not modified with azobenzene and does not have photoresponsive properties.
[0118] Other treatments: The pulsed laser etching parameters were incorrect, resulting in microgrooves that were too deep (20 μm) and too wide (80 μm) apart, which failed to achieve a synergistic effect. The processes for steps S20-S50 were chaotic and not carried out according to requirements.
[0119] Performance test: water contact angle 140°, oil contact angle 15°, oil absorption rate 15g / g, separation flux 6000L / (m 2 h) It has poor acid and alkali resistance, with performance dropping sharply after 50 cycles within the pH range of 2-12, with a retention rate of 50%. It cannot be used in optically controlled oil-water separation systems, and its effectiveness in oily wastewater treatment and marine oil spill emergency recovery is extremely poor. Its removal rate for emulsified oil with droplet sizes of 5-50 μm is only 50%.
[0120] The performance of the super-oleophilic and super-hydrophobic surface modified non-woven fabrics of the above four groups of examples and the two groups of comparative examples are compared, as shown in the following table:
[0121]
[0122] According to the above table data analysis:
[0123] 1. Water contact angle and oil contact angle
[0124] Example: The water contact angles of the four examples are all ≥160°, and the oil contact angles are ≤5°, showing excellent super-oleophilic and super-hydrophobic properties. Among them, the water contact angle of Example 3 is as high as 168°, and the hydrophilicity is the worst; the oil contact angle of Example 1 is the smallest at 3°, and the oleophilicity is the best. This shows that under appropriate process parameters, the wettability of the non-woven fabric surface can be effectively regulated so that it exhibits completely different affinity characteristics for water and oil. Comparative example: The water contact angles of Comparative Example 1 and Comparative Example 2 are 150° and 140°, respectively, which are much lower than those of the example; the oil contact angles are 10° and 15°, respectively, which are significantly higher than those of the example. This shows that the simplified or incorrect processes in the comparative examples, such as the failure to use a suitable transition layer, a simplified polyelectrolyte intermediate layer, etc., have seriously damaged the surface microstructure of the non-woven fabric, making it impossible to achieve good super-oleophilic and super-hydrophobic properties.
[0125] 2. Oil absorption rate
[0126] Examples: The oil absorption rates of the examples ranged from 24 to 30 g / g, with Example 3 achieving the highest oil absorption rate, reaching 30 g / g. This high oil absorption rate stems from the synergistic effect of the three-dimensional graded modified layers. The MOF nanoparticle layer increases the specific surface area, while the polyelectrolyte middle layer and the photoresponsive outer layer optimize the surface chemistry, enabling the nonwoven fabric to efficiently adsorb oils.
[0127] Comparative Examples: The oil absorption rate of Comparative Example 1 was 18 g / g, while that of Comparative Example 2 was only 15 g / g, far lower than that of the Example. In the Comparative Examples, the oil adsorption capacity of the nonwoven fabric was significantly reduced due to improper MOF nanoparticle loading and ineffective polyelectrolyte membrane formation.
[0128] 3. Separation flux
[0129] Example: The separation flux of the embodiment is 12200-13500L / (m 2 h), the separation flux of Example 3 is the highest. This is due to the directional oil-conducting channels constructed by the coordinated construction of the reasonable micro-groove array and nanostructure, as well as the good surface properties, which enable oil substances to pass through the non-woven fabric quickly and achieve efficient separation.
[0130] Comparative Example: The separation flux of Comparative Example 1 is 8000L / (m 2 ·h), while the comparative example 2 is only 6000L / (m 2 h). In the comparative example, due to poor surface structure and the lack of effective oil-conducting channels, the passage of oil substances was greatly hindered, resulting in low separation flux.
[0131] 4. Acid and alkali resistance
[0132] Example: All four examples maintained ≥90% performance after 500 acid and alkali (pH 2-12) cycles, with Example 3 achieving the highest performance retention of 93%. This is primarily due to the aluminum oxide protective layer deposited on the surface using ALD atomic layer deposition technology in step S50, which effectively enhanced the acid and alkali resistance of the non-woven fabric.
[0133] Comparative Examples: Comparative Example 1 retained only 70% of its performance after 100 cycles, while Comparative Example 2 retained only 50% after 50 cycles. The lack of key processes like the deposition of an alumina protective layer in these comparative examples made the nonwoven fabric susceptible to corrosion in acidic and alkaline environments, leading to a rapid decline in performance.
[0134] 5. Performance of light-controlled oil-water separation system
[0135] Example: In the light-controlled oil-water separation system of the examples, the separation efficiency was ≥95% after 500 light-responsive switching cycles, with the highest separation efficiency in Example 3 reaching 97%. This demonstrates that the rational design and preparation of the light-responsive outer layer in the examples enables the nonwoven fabric to achieve stable selective adsorption under UV / visible light switching, ensuring long-term separation performance.
[0136] Comparative Examples: Comparative Example 1 exhibited unstable photoresponsive switching, barely functioning after 500 cycles. Comparative Example 2 was unsuitable for use in a light-controlled oil-water separation system. The lack of azobenzene modification on the photoresponsive outer layer in this comparative example resulted in a lack of photoresponsive properties, making it unsuitable for light-controlled oil-water separation.
[0137] 6. Applicability to wide temperature range and emulsified oil removal rate
[0138] Examples: All four examples functioned properly over a wide temperature range of -40°C to 120°C, achieving a removal rate of ≥98% for emulsified oil droplets ranging from 5 to 50 μm. This excellent wide temperature range is attributed to the stability of the material's overall structure, while the high removal rate is attributed to its superoleophilic and superhydrophobic properties, as well as its microstructure's effective handling of the emulsified oil.
[0139] Comparative Examples: Comparative Example 1 exhibited unstable performance over a wide temperature range, while Comparative Example 2 performed poorly. The emulsified oil removal rates for the comparative examples were 70% and 50%, respectively, significantly lower than those for the examples. This was due to the overall poor performance of the comparative examples, which were unable to effectively handle a wide temperature range and emulsified oil.
[0140] In general, by comparing the data of the embodiments and comparative examples, it can be clearly seen that the embodiments prepared according to the standard process are significantly better than the comparative examples in various performances. Each process step is crucial to achieving the super oleophilic and super hydrophobic properties of the non-woven fabric and its performance in practical applications.
[0141] Advantages of the super-oleophilic and super-hydrophobic surface modified non-woven fabric of the present invention and its preparation method and application:
[0142] 1. Product performance
[0143] The super-oleophilic and super-hydrophobic properties are outstanding: the water contact angle is ≥160°, and the oil contact angle is ≤5°. It can clearly distinguish between water and oil in the oil-water mixed system and efficiently separate oil and water, greatly improving the practicality of non-woven fabrics in scenarios such as oily wastewater treatment and marine oil spill emergency recovery.
[0144] High oil absorption rate: The oil absorption rate reaches 24-30g / g. Thanks to the increased specific surface area of the MOFs nanoparticle layer and the optimization of the surface chemical properties by the polyelectrolyte middle layer and the light-responsive outer layer, it can absorb a large amount of oil substances, improve the ability to treat oil pollution in a single time, and reduce the number of treatment processes.
[0145] High separation flux: separation flux is 12200-13500L / (m 2 h), the directional oil-conducting channels constructed in collaboration with the reasonable micro-groove array and nanostructure, combined with good surface properties, enable oil substances to quickly pass through the non-woven fabric, greatly improving the oil-water separation efficiency and meeting the needs of large-scale industrial applications.
[0146] Excellent acid and alkali resistance: After 500 cycles of acid and alkali resistance (pH 2-12), the performance retention rate is ≥90%. The aluminum oxide protective layer deposited by ALD atomic layer deposition technology effectively enhances the acid and alkali resistance of the non-woven fabric, broadening its application range in different acid and alkali environments, for example, it has more advantages in chemical wastewater treatment.
[0147] Good light-control performance: In the light-controlled oil-water separation system, the separation efficiency is ≥95% after 500 light-response switching. The rational design and preparation of the light-responsive outer layer enables the non-woven fabric to stably achieve selective adsorption under ultraviolet / visible light switching, realizing precise and controllable oil-water separation operations, and can be applied to intelligent oil-water separation equipment.
[0148] Wide Temperature Range Applicability and High Emulsified Oil Removal Rate: The product operates across a wide temperature range of -40°C to 120°C, achieving a removal rate of ≥98% for emulsified oil droplets ranging from 5-50μm. The stable overall material structure ensures wide temperature range applicability. Its super-oleophilic and super-hydrophobic properties, combined with its microstructure, effectively treat emulsified oil, making it highly effective even in complex temperature environments, such as polar regions or high-temperature industrial environments.
[0149] 2. Preparation method
[0150] Strong process synergy: Through a series of steps, including substrate pretreatment, in-situ MOF growth, surface functionalization, interface enhancement, and functional synergistic modification, each process works in synergy. For example, substrate pretreatment provides a good foundation for the subsequent growth of MOF nanoparticles, while in-situ MOF growth determines key properties such as specific surface area. Subsequent surface functionalization further optimizes performance, resulting in a significant synergistic effect that significantly enhances product performance.
[0151] High parameter controllability: During the growth of MOFs, the addition of surfactants can adjust the uniformity of particle size (CV value <15%); the polyelectrolyte membrane is precisely controlled by controlling the deposition time of each layer (10-30min) and the solution concentration (0.5-2wt%); parameters such as the nano-titanium dioxide sol loading (1-3wt%) can be flexibly adjusted, making it easy to customize product performance according to different application requirements.
[0152] Innovative technological applications: A series of advanced technologies such as radio frequency magnetron sputtering to deposit titanium metal transition layer, layer-by-layer self-assembly technology to alternately deposit polyelectrolytes, ultraviolet light-induced polymerization to graft photoresponsive outer layer, carbon dioxide supercritical fluid treatment to promote interface fusion, pulsed laser deposition technology to etch micro-groove arrays, and ALD atomic layer deposition technology to deposit aluminum oxide protective layer are used to ensure the realization and improvement of product performance.
[0153] 3. Application
[0154] Application advantages of the light-controlled oil-water separation system: Selective adsorption can be achieved through ultraviolet / visible light switching, and it can provide efficient and precise separation operations in scenarios where precise control of oil-water separation is required, such as laboratory trace oil-water separation experiments and oil-water separation links on specific industrial production lines.
[0155] Advantages of oily wastewater treatment: Synchronous completion of oil-water separation and organic pollutant degradation. When treating oily wastewater, it can not only separate oil and water, but also use nano-titanium dioxide sol post-treatment to achieve a degradation rate of organic pollutants such as benzene series ≥ 90%, reduce secondary pollution, reduce subsequent treatment costs, and meet environmental protection requirements.
[0156] Marine Oil Spill Emergency Recovery Advantages: The removal rate for emulsified oil with a droplet size of 5-50μm is ≥98%. During marine oil spill emergency response, this device can quickly and efficiently recover emulsified oil, reducing marine environmental pollution and protecting marine ecosystems. Furthermore, it is recyclable, with a separation efficiency of ≥95% after 500 light response cycles. It is suitable for use in a wide temperature range of -40°C to 120°C, ensuring its effectiveness in diverse marine environments.
[0157] The basic principles, main features, and advantages of the present invention are shown and described above. It should be understood by those skilled in the art that the present invention is not limited to the above-described embodiments. The above-described embodiments and descriptions are merely preferred examples of the present invention and are not intended to limit the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention, and such changes and modifications fall within the scope of the invention claimed.
Claims
1. A super oleophilic and super hydrophobic surface modified nonwoven fabric, characterized in that: include: Non-woven fabric substrate: Made of PP polypropylene or PET polyester fibers with a diameter of 5-20 μm through needle punching / spunlace process, with a unit area mass of 80-200 g / m 2 ; Three-dimensional graded modified layer, comprising: MOFs nanoparticle layer: in situ grown ZlF-8 or MOF-5 nanoparticles, with a particle size of 30-80 nm, covalently bonded to the amino groups on the substrate surface through coordination bonds, with a thickness of 2-5 μm; Polyelectrolyte interlayer: 5-10 layers of PSS polystyrene sulfonate and PDDA polydiallyldimethylammonium chloride are alternately deposited, with a total thickness of 50-200 nm; Photoresponsive outer layer: Azobenzene-modified perfluoropolyether coating, grafting density ≥ 1.2 mmol / m 2 , the surface energy under UV irradiation dropped from 12mN / m to 8mN / m; The water contact angle of the modified non-woven fabric is ≥160°, the oil contact angle is ≤5°, the oil absorption rate is ≥25g / g, and the separation flux is ≥12000L / (m 2 h), acid and alkali resistance (pH 2-12) performance retention rate ≥ 90% after 500 cycles.
2. The super oleophilic and super hydrophobic surface modified nonwoven fabric according to claim 1, wherein The MOFs nanoparticles are in-situ grown by a solvent thermal method, with a loading amount of 30-50 wt%, and are chemically bonded to the non-woven fabric substrate via a titanium metal transition layer with a thickness of 5-20 nm, with a bonding strength of ≥5 N / cm.
3. The super oleophilic and super hydrophobic surface modified nonwoven fabric according to claim 1, wherein The photoresponsive outer layer is grafted by ultraviolet light-induced polymerization to form a cross-linked network with a thickness of 10-30 nm, and the wettability switching is completed within 30 seconds under 365 nm light.
4. The super oleophilic and super hydrophobic surface modified nonwoven fabric according to claim 1, wherein The surface of the modified non-woven fabric is etched by pulsed laser to form a micro-groove array with a depth of 5-15 μm, and the spacing between adjacent micro-grooves is 20-50 μm, which cooperates with the nanostructure to construct a directional oil guide channel.
5. A method for preparing a super oleophilic and super hydrophobic surface modified nonwoven fabric, for preparing the super oleophilic and super hydrophobic surface modified nonwoven fabric according to any one of claims 1 to 4, characterized in that: include: S10, substrate pretreatment: S11: immersing the non-woven fabric in an ethanol solution containing 0.1-2 wt% polyethyleneimine and ultrasonically treating the solution at 50-80° C. for 10-30 min to form a cationic adsorption layer; S12: depositing a 5-20 nm thick titanium metal transition layer on the substrate surface by radio frequency magnetron sputtering; S20, MOFs in situ growth: The pretreated non-woven fabric was immersed in a methanol solution containing 0.2-0.5M zinc nitrate and 0.5-1.0M 2-methylimidazole, and the reaction was hydrothermally reacted at 80-120°C for 6-18 hours. The pH was adjusted to 4.5-5.5 to form a ZIF-8 nanoparticle layer. The unreacted substances were removed by centrifugation and ethanol washing, and the MOFs-modified non-woven fabric was obtained after vacuum drying. S30, surface functionalization: S31: First, the MOFs-modified non-woven fabric is immersed in a toluene solution of 3-aminopropyltrimethoxysilane at a concentration of 1-5 wt % and reacted at 60-90° C. for 2-4 h to introduce amino active sites; S32: alternately depositing sodium polystyrene sulfonate and polydiallyldimethylammonium chloride using a layer-by-layer self-assembly technique to form a polyelectrolyte composite membrane with a thickness of 50-200 nm; S33: Finally, ultraviolet light-induced polymerization is performed to graft the perfluoropolyether containing azobenzene groups, with the grafting rate being controlled at 8-15 wt %; S40, interface strengthening treatment: The modified nonwoven fabric prepared in step S30 is placed in a carbon dioxide supercritical fluid at 10-20 MPa and 40-60° C. for 30-60 minutes to promote interface fusion of the materials; Pulsed laser deposition technology is used to etch micro-grooves on the surface with a depth of 5-15μm and a spacing of 20-50μm to form directional oil-conducting channels; S50, functional synergistic modification: Nano-titanium dioxide sol is introduced for post-treatment to generate hydroxyl radicals in situ on the surface of the non-woven fabric through photocatalytic reaction, achieving synergistic function of oil degradation; ALD atomic layer deposition technology is used to deposit a 5-10 nm thick aluminum oxide protective layer on the surface to enhance acid and alkali resistance, thereby obtaining the final super-oleophilic and super-hydrophobic surface modified non-woven fabric.
6. The method for preparing a super oleophilic and super hydrophobic surface modified nonwoven fabric according to claim 5, wherein In step S20 , a 0.01-0.05 M surfactant is added to the MOFs growth solution. The surfactant is CTAB hexadecyltrimethylammonium bromide to adjust the particle size uniformity, and the CV value is less than 15%.
7. The method for preparing a super oleophilic and super hydrophobic surface modified nonwoven fabric according to claim 5, wherein In step S30 , the polyelectrolyte membrane is formed by electrostatic adsorption, the deposition time of each layer is 10-30 minutes, and the solution concentration is 0.5-2 wt %.
8. The method for preparing a super oleophilic and super hydrophobic surface modified nonwoven fabric according to claim 5, wherein In step S50, the post-treatment of the nano-titanium dioxide sol is achieved by an immersion-pulling method, with a loading amount of 1-3 wt % and a degradation rate of benzene series substances under visible light of ≥90%.
9. An application of a super oleophilic and super hydrophobic surface modified nonwoven fabric, based on the super oleophilic and super hydrophobic surface modified nonwoven fabric according to any one of claims 1 to 4, characterized in that: Available for: Light-controlled oil-water separation system, which achieves selective adsorption through ultraviolet / visible light switching; Oily wastewater treatment, simultaneous completion of oil-water separation and organic pollutant degradation; Marine oil spill emergency recovery, the removal rate of emulsified oil with oil droplet size of 5-50μm is ≥98%.
10. The use of the super-oleophilic and super-hydrophobic surface modified non-woven fabric according to claim 9, characterized in that: The modified non-woven fabric can be recycled, and the separation efficiency is still ≥95% after 500 light response switchings, and is suitable for a wide temperature range environment of -40°C to 120°C.
Citation Information
Patent Citations
Self-cleaning polybenzoxazine super-hydrophobic super-oleophylic net film material and application in oil-water separation
CN106178599A